FINANCIAL MECHANISM OF DEVELOPMENT OF MICROENTREPRENEURSHIP - T. Dabbous (Вестник университета)
The article deals with the approaches to interpretation of a concept of the financial mechanism of development of micro-entrepreneurship. The financial mechanism of development of micro-entrepreneurship including three levels of his functioning is developed: state, market and internal, financial methods, tools and levers, and also system of providing the financial mechanism of development of a micro-entrepreneurship. Classification of the indicators characterizing formation of financial resources and results of economic activity of subjects of a micro-entrepreneurship is offered.